A cost function for Australia's railways - Wills-Johnson, Nick (Centre for Research in Applied Economics, Curtin Business School, 2009)
This paper utilises a unique dataset comprising of a hundred years of Australian railway history to develop a cost function for Australia?s railways. It explores two different functional forms, highlighting the advantages and disadvantages of each, and explores some of the ramifications of the cost models, both in terms of the economics of Australia?s railways and their economic regulation.